PERBANDINGAN TINGKAT KESEGARAN JASMANI ANTARA SISWA PUTRA KELAS XI IPS DENGAN SISWA PUTRA KELAS XI IPA SMA NEGERI 1 KUBU BABUSSALAM KAB. ROKAN HILIR - Yanto, Ermi; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine whether there is a comparison of the level of physical fitness between male students of class XI IPS with male students of class XI IPA at SMA Negeri 1 Kubu Babussalam, Rokan Hilir Regency. This type of research is a comparative study that compares one sample group with another sample group based on certain variables or measures. The population in this study is 42 students and it uses saturated sampling techniques. The instrument usedis in the form of the Indonesian Physical Fitness Test (TKJI) for children aged 16-19 years. The data analysis technique used is the